The Lex Favor Reo Principle After New Criminal Code: A Corrective Justice’s Perspective - Henny Saida Flora; Fradhana Putra Disantara; Mac Thi Hoai Thuong (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The purpose of this study is to analyze the existence and implications of the lex favor reo principle after the ratification of the new Criminal Code in relation to aspects of corrective justice. This research is normative legal research by prioritizing conceptual and statutory approaches. The results of the study show that the existence of the lex favor reo principle after the ratification of the new Criminal Code, namely as formulated in Article 3 juncto Article 618 of the new Criminal Code, the existence and applicability of the lex favor reo principle can be immediately enforced. The implication of the lex favor reo principle in optimizing aspects of corrective justice after the ratification of the new Criminal Code is that the implementation of the lex favor reo principle has implications for the existence of criminal sanctions experienced by defendants in the old Criminal Code. Suggestions in this study are that for law enforcement officials, special attention is needed when trying a crime, especially by first paying attention to the lex favor reo principle to see which sanctions are more profitable for the accused.